2021
DOI: 10.36090/e-dj.v2i2.824
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of UMKM tax collection at the west Makassar primary tax office

Abstract: “The effectiveness of UMKM tax collection at the west Makassar primary tax office”. The research published o/n the final project is aimed at recognizing the effectiveness of UMKM tax collection on western Makassar primary tax services.The type of research used is qualitative descriptive that writing describes the results of observation and analyses data obtained in the freld. Writing thefinal task is the result of research performed in May 2020 to june 2020.After analyzing and discussing a problem,The authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…However, in terms of potential obstacles, some informants experienced difficulties such as system errors and operational complications. This is in accordance with many studies such as Desi (2021), Andi (2021) and Arianty (2021) where usability and errors that occur in the system are the main problems encountered in all internet-based services such as e SPT and e Bupot. In terms of features, it was found that e Bupot provides features that support all taxpayer transaction needs.…”
Section: Quality Of the E-bupot Systemsupporting
confidence: 91%
“…However, in terms of potential obstacles, some informants experienced difficulties such as system errors and operational complications. This is in accordance with many studies such as Desi (2021), Andi (2021) and Arianty (2021) where usability and errors that occur in the system are the main problems encountered in all internet-based services such as e SPT and e Bupot. In terms of features, it was found that e Bupot provides features that support all taxpayer transaction needs.…”
Section: Quality Of the E-bupot Systemsupporting
confidence: 91%